2012
DOI: 10.4491/eer.2012.17.1.047
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nonpoint Source Pollution Runoff from Urban Land Uses in South Korea

Abstract: A long-term nationwide nonpoint-source pollution monitoring program was initiated by the Ministry of Environment Republic of Korea (ME) in 2007. Monitoring devices including rain gauges, flow meters, and automatic samplers were installed in monitoring sites to collect dynamic runoff data in 2008-2009. More than 10 rainfall events with three or more antecedent dry days were monitored per year. More than 10 samples were collected and analyzed per event. So far, five land use types (single family, apartments, edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…A urbanização e os processos derivados, como a impermeabilização do solo e a artificialização da drenagem natural das águas, são amplamente conhecidos como os causadores de diversos impactos ambientais (BUTLER & DAVIES, 2004;PACHECO & LIMA NETO, 2017, ARAÚJO & LIMA NETO, 2018ARAÚJO et al, 2019). Aliado aos aspectos culturais das populações locais e à dinâmica própria do ambiente natural, as bacias hidrográficas urbanas oferecem respostas compatíveis com as diversas formas de uso e ocupação do solo, bem como com a gestão do ambiente urbano (ARMITAGE & ROOSEBOOM, 2000;MARAIS & ARMITAGE, 2004;ZEILHOFER;LIMA, 2010;NEVES & TUCCI, 2011;RHEE et al, 2012;ARORA & REDDY, 2013;SIDHU et al, 2013;SILVA & PORTO, 2015).…”
Section: Introductionunclassified
“…A urbanização e os processos derivados, como a impermeabilização do solo e a artificialização da drenagem natural das águas, são amplamente conhecidos como os causadores de diversos impactos ambientais (BUTLER & DAVIES, 2004;PACHECO & LIMA NETO, 2017, ARAÚJO & LIMA NETO, 2018ARAÚJO et al, 2019). Aliado aos aspectos culturais das populações locais e à dinâmica própria do ambiente natural, as bacias hidrográficas urbanas oferecem respostas compatíveis com as diversas formas de uso e ocupação do solo, bem como com a gestão do ambiente urbano (ARMITAGE & ROOSEBOOM, 2000;MARAIS & ARMITAGE, 2004;ZEILHOFER;LIMA, 2010;NEVES & TUCCI, 2011;RHEE et al, 2012;ARORA & REDDY, 2013;SIDHU et al, 2013;SILVA & PORTO, 2015).…”
Section: Introductionunclassified
“…Non-point source (NPS) pollution is the main cause of inland water deterioration and a priority issue for present water quality management worldwide [1,2]. NPS pollution is more difficult to control and to treat than pollution from point sources due to the complicated generation and formation [3,4] and concern for NPS pollution affecting lake water quality has continually increased [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the characteristics of the study area, there are many commercial activities in the commercial area, and daily life in the residential area, which will generate a lot of domestic waste. Previous studies have found that the runoff from the residential area has significant concentrations of organic carbon (Rhee et al, 2012;Salim et al, 2019).…”
Section: Seasonal and Regional Source Identificationmentioning
confidence: 99%